The Past, Present, and Future of Cartulary Studies: JMMS at IMC 2024 - Burton, Janet (The journal of medieval monastic studies, 2025)
This joint article presents in published form papers delivered at the Leeds International Medieval Congress in 2024 as well as expanding on aspects of the roundtable discussion that complemented the panel. They encompass a whole range of issues, choices, challenges, and decisions, that may confront both editors and users of cartularies. Together, they reflect the revolution that has taken place in cartulary studies over recent years. Rooted in several case studies of recent and ongoing cartulary editing and analysis, this article sets out how the authors have approached a variety of cartulary manuscripts through close analysis of their form, structure, palaeography, and contents, and in so doing illuminates how researchers can nuance their approaches to these challenging manuscripts.